Experiments on mineral carbonation of CO2 in gabbro from the Sines massif – first results of project InCarbon - Moita, Patrícia (2020)
The InCarbon project based on the principles of CO2 capture and storage technologies, aims to study the potential of in situ mineral carbonation in mafic rocks in Alentejo. The gabbro of Sines massif was selected for the first laboratory test of mineral carbonation due to its geochemical, mineralogical and textural characteristics and proximity to the main focus of CO2 emissions in the region. Gabbro specimens were submerged in natural brine and supercritical CO2 for periods of 1, 4, 16 and 64 days, under 80 bar and 40 ºC. The specimens were characterized before and after the experiments by means of XRD, OM, VP-SEM-EDS and ATR-FTIR, and the brine composition was analysed. Results show dissolution of silicates and textural roughness increasing with the number of days of immersion into brine. The behaviour of cations in solution after several days of testing is irregular and carbonate precipitation was not detected.